2008
DOI: 10.3201/eid1406.071586
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and Temporal Evolution of Bluetongue Virus in Wild Ruminants, Spain

Abstract: We confi rmed the emergence of bluetongue virus (BTV) in 5 wild ruminant species in Spain. BTV seroprevalence was high and dispersed with time, with a south-tonorth gradient. Our results suggest a complex epidemiology of BTV and underline the need for additional research on wildlife in Europe.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
77
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(87 citation statements)
references
References 12 publications
8
77
1
1
Order By: Relevance
“…The clinical signs of BT were also produced after experimental infection of pronghorn antelope (Antilocapra Americana), American bison (Bison bison), and African buffalo (Syncerus caffer) (Tessaro and Clavijo, 2001). Under natural conditions the disease may also be present in wapiti (Cervus elaphus canadensis), axis deer (Axis axis), fellow deer (Dama dama), sika deer (Cervus nippon), musk deer (Moschus moschiferus), roe deer (Capreolus capreolus), Spanish ibex (Capra pyrenaica), and captive yak (Bos grunniens grunniens (Howerth et al 2001, Fernandez-Pacheco et al 2008, Ruiz-Fons et al 2008, Rodriquez-Sanchez et al 2010. BTV infection, antibody response and clinical disease (Work et al 1992) (Table 1).…”
Section: Bluetongue In Wildlifementioning
confidence: 99%
See 3 more Smart Citations
“…The clinical signs of BT were also produced after experimental infection of pronghorn antelope (Antilocapra Americana), American bison (Bison bison), and African buffalo (Syncerus caffer) (Tessaro and Clavijo, 2001). Under natural conditions the disease may also be present in wapiti (Cervus elaphus canadensis), axis deer (Axis axis), fellow deer (Dama dama), sika deer (Cervus nippon), musk deer (Moschus moschiferus), roe deer (Capreolus capreolus), Spanish ibex (Capra pyrenaica), and captive yak (Bos grunniens grunniens (Howerth et al 2001, Fernandez-Pacheco et al 2008, Ruiz-Fons et al 2008, Rodriquez-Sanchez et al 2010. BTV infection, antibody response and clinical disease (Work et al 1992) (Table 1).…”
Section: Bluetongue In Wildlifementioning
confidence: 99%
“…The highest titres of BTV antibodies have been detected in samples of sera taken from free-ranging European red deer and fallow deer (Dama dama) from Cervinae subfamily (Ruiz-Fons et al 2008, Garcia et al 2009, Linden et al 2009). The RNA of BTV serotype 8 was detected by Real-Time RT-PCR (rRT-PCR) in naturally-infected wild deer in Belgium (Linden et al 2008) and BTV1 and BTV4 genetic material in blood of European red deer and mouflons in Spain (Garcia et al 2009) while BTV1 and BTV8 RNA in red deer in France (Rossi et al 2010).…”
Section: Bluetongue In Wildlifementioning
confidence: 99%
See 2 more Smart Citations
“…The inclusion of processes beyond wind alone, however, considerably increases the complexity of the models involved, and often reduces our ability to understand the relative importance of each of the many factors potentially involved in the 2006 outbreak: midge flight capability [17], local spatial scale dynamics and characteristics (topography, land use, farm management, etc. [18]), climate [19], virus mutation rate [20], vector competence for specific virus serotypes, transmission parameters and incubation period [21]. Moreover, there are no direct measurements of how wind affects midge flight, although it might be expected that small insects such as Culicoides have limited flight capacity and are unlikely to take off and fly at all above certain wind speeds, as suggested by the negative correlation between midge numbers (or rate of midge biting on hosts, as in Carpenter et al [17]) and wind speed found for the obsoletus group, common Culicoides spp.…”
Section: Introductionmentioning
confidence: 99%